Optimising base locations for New Zealand's Helicopter Emergency Medical Services. (August 2021) - de Graaf, Brandon; Lilley, Rebbecca; Davie, Gabrielle; Kool, Bridget
Highlights: Mathematical optimization improves helicopter emergency medical services placement. 113, 886 additional people in New Zealand could reach a hospital within one hour. Especially beneficial for indigenous Māori as well as deprived and rural communities. Abstract: Helicopter Emergency Medical Services (HEMS) in New Zealand (NZ) are located at hospitals or airports near the communities they serve. This may result in suboptimal response times. Timely access to advanced hospital care improves critically injured patients' chances of survival. This study optimised the location of HEMS bases in NZ and compared current versus optimal placement on timely access for surrounding populations. Optimal placement of HEMS bases could result in 113, 886 additional people (3% of the population) benefiting from access to advanced hospital care within one hour. Optimal placement would especially benefit indigenous Māori as well as deprived and rural communities.